Understanding ASEAN Centrality: Comparative Analysis of ‘Core’ and ‘Hub’ Strategies - Shintaro Hamanaka (Asia & the Pacific Policy Studies)
ABSTRACT ASEAN centrality is a term that has emerged in the recent literature on international relations and institutions focussing on the region surrounding ASEAN. It refers to the idea that ASEAN has or should have a central role in forming the political and economic institutional architecture of a wider region. Unfortunately, however, previous studies have failed to identify whether ASEAN has centrality or not. There are two problems. First, the concept of centrality is vague. Second, a sound method to assess the centrality is absent. This study attempts to contribute to the literature mainly from theoretical (conceptual) and, to a lesser degree, empirical perspectives. From the theory front, the paper elaborates the notion of centrality, by differentiating the two concepts related to centrality: core and hub. From the empirical front, the paper claims the usefulness of comparative analysis. Even if the level of centrality cannot be measured, we can better assess whether ASEAN hold the core and/or hub status in regional institutional architecture, if it is compared with other institutions.